A Comparative Legal Study of Commissioner and Shareholder Authority over Director Negligence Case: Indonesia vs. Singapore - Putri Saphira Audesti Binti Yussofi; Triana Dewi Seroja; Rufinus Hotmaulana Hutauruk (Universitas Internasional Batam, 2024)
In terms of conducting business interactions through a PT, it is not uncommon for investors from Indonesia and Singapore to experience disharmony in practice, such as negligence by the board of directors that results in harm to the company. Therefore, it is important to have an effective legal mechanism to challenge such negligence so there is an urgency to identify and understand the differences between the legal framework in Indonesia and Singapore in dealing with directors' negligence is important for stakeholders to adopt best practices and improve corporate governance. The results show that derivative rights in Singapore provide a more effective and efficient tool for shareholders to challenge directors' negligence, with clearer legal procedures and stronger legal protections compared to Indonesia. The study concludes that the adoption of best practices from Singapore can improve corporate accountability and governance in Indonesia.